2003
DOI: 10.1111/j.1349-7006.2003.tb01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based study of relationship between hospital surgical volume and 5‐year survival of stomach cancer patients in Osaka, Japan

Abstract: Despite the large number of surgical operations for stomach cancer in Japan, no study based on data from population-based cancer registries has been conducted regarding the relationship between hospital surgical volume for stomach cancer and patients' survival. Using data from the Osaka Cancer Registry (OCR), we performed survival analyses on 28,608 patients aged 35-79 years old who underwent surgery for stomach cancer, according to the extent of disease at diagnosis (localized: cancer is confined to the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…North American series have reported 14 or 15 gastric cancer cases per year as a marker of a high-volume gastric cancer center [27,34]. In Asia, 200 cases per year are considered a marker of a high-volume institution [37][38][39]. Gastric cancer surgery has been centralized in some countries such as the UK, Denmark, The Netherlands, Sweden, and Finland [40].…”
Section: Discussionmentioning
confidence: 99%
“…North American series have reported 14 or 15 gastric cancer cases per year as a marker of a high-volume gastric cancer center [27,34]. In Asia, 200 cases per year are considered a marker of a high-volume institution [37][38][39]. Gastric cancer surgery has been centralized in some countries such as the UK, Denmark, The Netherlands, Sweden, and Finland [40].…”
Section: Discussionmentioning
confidence: 99%
“…Eligibility criteria included: (1) adenocarcinoma of the stomach, (2) patients with stage I-III disease who underwent gastrectomy with curative intent, (3) no history of gastrectomy or other malignancy and (4) no history of neoadjuvant chemotherapy. Ultimately, 976 patients were included in this study.…”
Section: Patients and Surgeonsmentioning
confidence: 99%
“…Although the prognosis of gastric cancer after surgery is mainly associated with tumor stage and other clinicopathological features, there is a growing consensus in the surgical literature that enhanced surgical technique and rich experience can improve outcomes for patients with curatively resected gastrointestinal cancer. Previous volume-outcome studies of patients with resectable gastric cancer have shown a positive association of surgical outcome with the hospital volume [1][2][3][4]. Compared with hospital volume, surgeon specialization can better predict surgical outcome in a given center.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a Dutch study showed that high hospital volume was associated with long‐term survival after esophagectomy, but not after gastrectomy 37. A Japanese study showed that in patients with localized or regionally metastasized gastric cancer, 5‐year survival between 1975 and 1979 was worse when resection was carried out at very low‐volume hospitals compared to high‐volume hospitals 34. This correlation, however, decreased in later time periods and disappeared in the period between 1990 and 1994, except for very low‐volume hospitals.…”
Section: Resultsmentioning
confidence: 96%
“…Since the 2000s, nine studies that each included at least 1000 patients have focused on long‐term survival after gastrectomy (Table 3), and four of these found a significant relationship between survival and hospital volume 23, 34, 35, 36. In a study from the USA showing a positive relationship between hospital volume and long‐term outcomes (HR, 0.82; 95% CI, 0.73–0.92; P <.001), differences in outcomes could not be explained by discrepancies in patient characteristics or operative mortality, suggesting that hospital volume was an independent predictor of long‐term survival after gastrectomy 35.…”
Section: Resultsmentioning
confidence: 99%